2019
DOI: 10.3389/fmicb.2019.02643
|View full text |Cite
|
Sign up to set email alerts
|

Novel Angiotensin-Converting Enzyme-Inhibitory Peptides From Fermented Bovine Milk Started by Lactobacillus helveticus KLDS.31 and Lactobacillus casei KLDS.105: Purification, Identification, and Interaction Mechanisms

Abstract: Fermented milks with strong angiotensin I-converting enzyme (ACE)-inhibitory activity were obtained through a culture with Lactobacillus helveticus KLDS.31 and Lactobacillus casei KLDS.105 with a fermentation and storage temperature of 37 °C. Ultrafiltration fractions with a molecular weight less than 3 kDa in fermented milk whey exhibited the strongest inhibitory activity. Correspondingly, a gastrointestinal digestion experiment showed retention of the bioactivity of these fractions with pepsin and trypsin tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 36 publications
0
28
0
1
Order By: Relevance
“…41 Some lactobacilli have been reported to release peptides with high affinity for ACE during milk fermentation. 42 Although the mechanism supporting the antiviral activity of L. paracasei DG observed in this study is not known, we can speculate that the unique rhamnose-rich heteroexopolysaccharide molecule that covers the cells of this bacterium may contribute to the peculiar cross-talk of DG with host cells. 43 Indeed, a limitation of our study was the inability to determine the essential molecules produced by L. paracasei DG required to inhibit SARS-CoV-2 replication.…”
Section: Discussionmentioning
confidence: 62%
“…41 Some lactobacilli have been reported to release peptides with high affinity for ACE during milk fermentation. 42 Although the mechanism supporting the antiviral activity of L. paracasei DG observed in this study is not known, we can speculate that the unique rhamnose-rich heteroexopolysaccharide molecule that covers the cells of this bacterium may contribute to the peculiar cross-talk of DG with host cells. 43 Indeed, a limitation of our study was the inability to determine the essential molecules produced by L. paracasei DG required to inhibit SARS-CoV-2 replication.…”
Section: Discussionmentioning
confidence: 62%
“…For instance, during milk fermentation, Lactobacillus helveticus and Lactobacillus casei release peptides with high affinity for ACE. Bovine milk fermented with Lactobacillus species yields fermented products enriched with ACE-inhibitory peptides ( 66 ), of which many are resistant to GI digestion and inhibit ACE in the renin-angiotensin system (RAS). In vitro and in vivo experiments have demonstrated antihypertensive effects of fermented milk products ( 67 , 68 ).…”
Section: Probiotics and Vitamin Dmentioning
confidence: 99%
“…Laboratory studies have reported that certain probiotics have anti-viral effects including against other forms of coronavirus ( Chai et al, 2013 ). Others have reported the potential of probiotics to interact with ACE2, the host entry receptor of SARS-CoV-2 virus; for instance, some lactobacilli have been reported to release peptides with high affinity for ACE during milk fermentation ( Li et al, 2019 ). Recently, Paenibacillus bacteria were shown to naturally produce carboxypeptidases homologous to ACE2 in structure and function ( Minato et al, 2020 ).…”
Section: Role Of Probiotics and Sars-cov-2 Infectionmentioning
confidence: 99%